2008
DOI: 10.1016/j.phrs.2008.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Dual roles of Nrf2 in cancer

Abstract: In response to oxidative stress, the transcription factor NF-E2-related factor 2 (Nrf2) controls the fate of cells through transcriptional upregulation of antioxidant response element (ARE)-bearing genes, including those encoding endogenous antioxidants, phase II detoxifying enzymes, and transporters. Expression of the Nrf2-dependent proteins is critical for ameliorating or eliminating toxicants/carcinogens to maintain cellular redox homeostasis. As a result, activation of the Nrf2 pathway, by naturally-occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
498
0
10

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 600 publications
(517 citation statements)
references
References 149 publications
(163 reference statements)
9
498
0
10
Order By: Relevance
“…As our manual curation contained more than three times the number of interactions for NRF2 than the already existing databases, and 81% of the predicted interactions are novel, we believe that our compilation could provide an efficient resource for the biomedical research on NRF2. This resource could facilitate network pharmacological attempts [50], including a multi-target concept [51,52] and the recently proposed allo-network drug concepts [53] and may help to overcome challenges in targeting NRF2 which is a double-edged sword in many diseases; that is, the activation of NRF2 in healthy cells could delay or prevent the onset of some forms of human cancers [54], while its constitutive activation is responsible for acquired chemoresistance in tumor cells [13,55]. Thus, we believe that a more detailed, dynamical understanding of the NRF2 interactome, regulome and fine-tuned regulatory loops will help to develop more potent NRF2 activator and inhibitor therapeutic agents.…”
Section: Resultsmentioning
confidence: 99%
“…As our manual curation contained more than three times the number of interactions for NRF2 than the already existing databases, and 81% of the predicted interactions are novel, we believe that our compilation could provide an efficient resource for the biomedical research on NRF2. This resource could facilitate network pharmacological attempts [50], including a multi-target concept [51,52] and the recently proposed allo-network drug concepts [53] and may help to overcome challenges in targeting NRF2 which is a double-edged sword in many diseases; that is, the activation of NRF2 in healthy cells could delay or prevent the onset of some forms of human cancers [54], while its constitutive activation is responsible for acquired chemoresistance in tumor cells [13,55]. Thus, we believe that a more detailed, dynamical understanding of the NRF2 interactome, regulome and fine-tuned regulatory loops will help to develop more potent NRF2 activator and inhibitor therapeutic agents.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that Nrf2 protects against oxidative stress, chemotherapeutic agents and radiotherapy (Lau et al 2008;Kensler and Wakabayashi 2010;Takahashi et al 2015). However, Nrf2 disruption has enabled the cells towards carcinogens, which lead to the progression of inflammation and, finally, cancer formation (Slocum and Kensler 2011;Takahashi et al 2015).…”
Section: Role Of the Nrf2-keap1 Pathway In Cancermentioning
confidence: 99%
“…However, Nrf2 disruption has enabled the cells towards carcinogens, which lead to the progression of inflammation and, finally, cancer formation (Slocum and Kensler 2011;Takahashi et al 2015). This dual action of Nrf2 has been termed as a 'double-edged sword' with respect to the benefits or risks of the Keap1-Nrf2 pathway in cells (Lau et al 2008). The Nrf2 transcription factor is associated with the phase II enzymes gene regulation, as it maintains the appropriate level of these enzymes inside the cell.…”
Section: Role Of the Nrf2-keap1 Pathway In Cancermentioning
confidence: 99%
“…The mechanism of resistance involves mutation or overexpression of target proteins, as well as decreased bioavailability of drugs caused by impaired uptake or enhanced detoxification (Ren et al, 2011). Recent studies have suggested that nuclear factor erythroid 2-related factor 2 (Nrf2), a basic leucine zipper transcription factor, could be an important contributor to chemoresistance (Lau et al, 2008). In fact, mutations in Nrf2 or related signaling molecules are found in many types of cancers, where they cause an increase in Nrf2 activity and are associated with resistance to chemotherapy (Sporn and Liby, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Because oxidative stress is implicated in the initiation and progression of cancer, activation of Nrf2 signaling has been considered as an useful strategy for chemoprevention (Giudice et al, 2010). However, more recently, high constitutive expression of Nrf2 has been observed in many types of cancer cells showing resistance to anti-cancer drugs (Lau et al, 2008). Many anti-cancer drugs induce apoptosis by producing reactive oxygen species (ROS) in cancer cells; therefore, its antioxidant and cytoprotective potential could be considered the 'dark side' of Nrf2 signaling as regards the therapeutic action of these drugs.…”
Section: Introductionmentioning
confidence: 99%